PERAN LINGKUNGAN BELAJAR DALAM PENGEMBANGAN SOSIAL-EMOSIONAL ANAK USIA DINI: TELAAH SISTEMATIS BERBASIS METODE KURIKULUM MERDEKA - Kurnia, Asraf; Iffah, Izzatul; Wahidi, Rosid; Selpiyana, Dede; Oviensy, Vegia (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to explore the role of the learning environment in supporting the socio-emotional development of early childhood within the context of the Kurikulum Merdeka. A positive learning environment has been proven to significantly contribute to the development of children's socio-emotional skills, such as communication, empathy, and emotional regulation. Using a Systematic Literature Review (SLR) approach, this research analyzed 25 articles published between 2018 and 2025 from various indexed journals. The findings reveal that positive interactions with teachers and peers, active parental involvement, and the integration of educational games significantly support the formation of children's socio-emotional skills. The Kurikulum Merdeka provides significant opportunities through project-based learning and activities tailored to children's developmental needs. However, challenges such as teachers' limited understanding of the approach and inadequate educational facilities remain significant obstacles. Collaboration between schools and families, along with continuous teacher training, is essential to optimize the implementation of the Kurikulum Merdeka in fostering early childhood socio-emotional development. Keywords: Socio-Emotional Development; Early Childhood; Kurikulum Merdeka; Systematic Literature Review.